Research on Business Model Transformation of Traditional Retail Enterprises under the Background of Digital Economy (Journal of Global Humanities and Social Sciences, 2024)
With the rapid development of Internet technology, the global economy is gradually entering the digital era, and traditional industries are facing unprecedented challenges and opportunities. The retail industry, as an important part of it, is experiencing the change from traditional business a model to digital transformation to adapt to the changing market environment and consumer demand. This paper discusses the path of business model transformation of traditional retail enterprises in the context of digital economy, emphasizes the necessity and urgency of business model transformation, and points out that the only way for enterprises to maintain competitiveness and achieve sustainable development in the fierce market competition is through digital transformation. The path of transformation practice includes the dimensions of online-offline integration, digital supply chain management, data-driven precision marketing, and innovative payment and settlement methods. By combining specific cases in the Philippine market, practical transformation strategies and theoretical guidance are provided for traditional retail enterprises to help them realize a new round of growth in the era of digital economy.